Binge-Drinking Attitudes and Behaviors Among Hispanic and Non-Hispanic College Students: Suggestions for Tailoring Health Campaign Messages. (May 2016) - Shields, Julie Delaney; Archiopoli, Ashley M.; Bentley, Joshua M.; Weiss, David; Hoffmann, Jeffrey; White, Judith McIntosh; Sharp, Mercedes Kelsey; Hong, Zhibin; Kimura, Miwa
This study explores binge-drinking behaviors and attitudes among Hispanic and non-Hispanic college students. The authors surveyed students at the same large Hispanic-serving university used in a 1999 study by Bennett et al., partially replicating that earlier research. While the percentage of students who reported binge drinking in the present study did not differ significantly by ethnicity, Hispanic students showed the most dramatic decrease in binge-drinking behavior since the 1990s study. Perhaps not coincidentally, during the years between studies, the university's substance-abuse prevention office increased its outreach and awareness programs; university policies concerning alcohol use became more stringent and more publicly promoted; and Hispanics became the largest segment of the school's undergraduate population. At the same time, despite these contextual changes, Hispanic students in the present study were less likely than other groups to disagree with the statement "binge drinking is part of my race/culture, " while non-Hispanic White students were less likely to disagree with the statement "no one ever died as a result of binge drinking." Recommendations for binge-drinking education and prevention campaigns explicitly targeting Hispanic students and other risk groups (students living on campus; students from rural areas) are discussed.